Expression of androgen receptor and its phosphorylated forms in breast cancer progression. Issue 14 (19th April 2013) - Ren, Qinghu; Zhang, Liying; Ruoff, Rachel; Ha, Susan; Wang, Jinhua; Jain, Shilpa; Reuter, Victor; Gerald, William; Giri, Dilip D.; Melamed, Jonathan; Garabedian, Michael J.; Lee, Peng; et al.
<x xml:space="preserve">Abstract</x> BACKGROUND Androgen receptor (AR) expression in breast cancers may serve as a prognostic and predictive marker. We examined the expression pattern of AR and its phosphorylated forms, Ser‐213 (AR‐Ser[P]‐213) and Ser‐650 (AR‐Ser[P]‐650), in breast cancer and evaluated their association with clinicopathological parameters. METHODS Immunohistochemistry was performed on primary and distant metastatic breast cancers and benign breast tissue using antibodies against AR, AR‐Ser(P)‐213, and AR‐Ser(P)‐650. The levels of cytoplasmic and nuclear expression were scored semiquantitatively using a histoscore. RESULTS Nuclear staining of AR was observed in all benign breast tissue and 67% of cancer cases. Nuclear and cytoplasmic AR‐Ser(P)‐213 was increased in breast cancers 2‐fold (P = .0014) and 1.7‐fold (P = .05), respectively, compared with benign controls, whereas nuclear and cytoplasmic AR‐Ser(P)‐650 expression was decreased in tumors by 1.9‐fold and 1.7‐fold (both P < .0001), respectively. Increased expression of nuclear or cytoplasmic AR‐Ser(P)‐213 was observed in metastatic breast cancers (1.3‐fold, P = .05), ER‐negative (2.6‐fold, P = .001), and invasive ductal carcinoma (6.8‐fold, P = .04). AR‐Ser(P)‐650 expression was downregulated in lymph node‐positive breast cancers (1.4‐fold, P = .02) but was upregulated in invasive ductal carcinomas (3.2‐fold, P < .0001) and metastases (1.5‐fold, P = .003). Moreover, in ER‐negative breast cancers, nuclear AR‐Ser(P)‐650 was decreased (1.4‐fold, P = .005), and cytoplasmic AR‐Ser(P)‐650 was increased (1.4‐fold, P = .003). CONCLUSIONS AR and its phosphorylation at serines 213 and 650 are differentially expressed in breast cancer tumorigenesis and progression. Phosphorylation of AR at serines 213 and 650 is increased in ER‐negative breast cancers, ductal carcinomas, and metastases and may have predictive value in breast cancer prognosis. Cancer 2013;119:2532–2540. © 2013 American Cancer Society.